﻿ 一个半离散非齐次核的Hilbert型不等式
 文章快速检索 高级检索
 浙江大学学报(理学版)  2017, Vol. 44 Issue (3): 292-295  DOI:10.3785/j.issn.1008-9497.2017.03.008 0

### 引用本文 [复制中英文]

[复制中文]
YANG Bicheng, CHEN Qiang. A half-discrete Hilbert-type inequality with a non-homogeneous kernel[J]. Journal of Zhejiang University(Science Edition), 2017, 44(3): 292-295. DOI: 10.3785/j.issn.1008-9497.2017.03.008.
[复制英文]

### 文章历史

1. 广东第二师范学院 数学系, 广东 广州510303;
2. 广东第二师范学院 计算机科学系, 广东 广州510303

A half-discrete Hilbert-type inequality with a non-homogeneous kernel
YANG Bicheng1 , CHEN Qiang2
1. Department of Mathematics, Guangdong University of Education, Guangzhou 510303, China;
2. Department of Computer Science, Guangdong University of Education, Guangzhou 510303, China
Abstract: By introducing independent parameters and applying the method of weight functions and technique of real analysis, a half-discrete Hilbert-type inequality with a non-homogeneous kernel and a best possible constant factor is provided. The equivalent forms with the best possible constant factors are considered.
Key words: Hilbert-type inequality    parameter    weight function    equivalent form    reverse

p > 1, $\frac{1}{p} + \frac{1}{q} = 1$, am, bn≥0(m, nN={1, 2, …}), 0 < $\sum\limits_{m = 1}^\infty {{a_m}^p}$ < ∞, 0 < $\sum\limits_{n = 1}^\infty {{b_n}^p}$ < ∞, 则有如下具有最佳常数因子$\text{ }\!\!\pi\!\!\text{ }/\text{sin}\left( \frac{\text{ }\!\!\pi\!\!\text{ }}{p} \right)$的Hardy-Hilbert不等式[1]:

 $\sum\limits_{n = 1}^\infty {\sum\limits_{m = 1}^\infty {\frac{{{a_m}{b_n}}}{{m + n}}} } < \frac{\pi }{{\sin \left( {\frac{\pi }{p}} \right)}}{\left( {\sum\limits_{m = 1}^\infty {a_m^p} } \right)^{\frac{1}{p}}}{\left( {\sum\limits_{n = 1}^\infty {b_n^p} } \right)^{\frac{1}{q}}}.$ (1)

 $\sum\limits_{n = 1}^\infty {\sum\limits_{m = 1}^\infty {\frac{{{a_m}{b_n}}}{{{U_m} + {V_n}}}} } < \frac{\pi }{{\sin \left( {\frac{\pi }{p}} \right)}}{\left( {\sum\limits_{m = 1}^\infty {\frac{1}{{\mu _m^{p - 1}}}a_m^p} } \right)^{\frac{1}{p}}}{\left( {\sum\limits_{n = 1}^\infty {\frac{1}{{v_n^{q - 1}}}b_n^p} } \right)^{\frac{1}{q}}}.$ (2)

μi=νi=1(iN)时, 式(2) 变为式(1)(文献[2]并没有证明式(2) 及确定常数因子的最佳性).

 $\begin{array}{l} 0 < {\lambda _i} \le 1\left( {i = 1,2} \right),{\lambda _1} + {\lambda _2} = {\lambda _\alpha },{a_m},{b_n} \ge 0,\\ 0 < \sum\limits_{m = 1}^\infty {{m^{p\left( {1 - {\lambda _1}} \right) - 1}}a_m^p} < \infty ,0 < \sum\limits_{n = 1}^\infty {{n^{q\left( {1 - {\lambda _2}} \right) - 1}}b_n^q} < \infty , \end{array}$

 $\begin{array}{l} \sum\limits_{n = 1}^\infty {\sum\limits_{m = 1}^\infty {\frac{{{a_m}{b_n}}}{{{{\left( {{m^\alpha } + {n^\alpha }} \right)}^\lambda }}}} } < \frac{1}{\alpha }B\left( {\frac{{{\lambda _1}}}{\alpha },\frac{{{\lambda _2}}}{\alpha }} \right) \times \\ {\left( {\sum\limits_{m = 1}^\infty {{m^{p\left( {1 - {\lambda _1}} \right) - 1}}a_m^p} } \right)^{\frac{1}{p}}}{\left( {\sum\limits_{n = 1}^\infty {{n^{q\left( {1 - {\lambda _2}} \right) - 1}}b_n^q} } \right)^{\frac{1}{q}}}, \end{array}$ (3)

 $B\left( {u,v} \right): = \int_0^\infty {\frac{1}{{{{\left( {t + 1} \right)}^{u + v}}}}{t^{u - 1}}{\rm{d}}t} \left( {u,v > 0} \right).$ (4)

α=λ=1, λ1=$\frac{1}{q}$, λ2= $\frac{1}{p}$时, 式(3) 变为式(1).文献[5-6]系统论述了参量化离散的Hilbert型不等式理论.文献[7]给出了式(2) 及式(3) 的具有最佳常数因子的推广式:

 $\begin{array}{l} \sum\limits_{n = 1}^\infty {\sum\limits_{m = 1}^\infty {\frac{{{a_m}{b_n}}}{{{{\left( {U_m^\alpha + V_n^\alpha } \right)}^\lambda }}}} } < \frac{1}{\alpha }B\left( {\frac{{{\lambda _1}}}{\alpha },\frac{{{\lambda _2}}}{\alpha }} \right) \times \\ \;\;\;\;\;\;\;{\left[ {\sum\limits_{m = 1}^\infty {\frac{{U_m^{p\left( {1 - {\lambda _1}} \right) - 1}}}{{\mu _m^{p - 1}}}a_m^p} } \right]^{\frac{1}{p}}}{\left[ {\sum\limits_{n = 1}^\infty {\frac{{V_n^{q\left( {1 - {\lambda _2}} \right) - 1}}}{{v_n^{q - 1}}}b_n^q} } \right]^{\frac{1}{q}}}. \end{array}$ (5)

μi=νi=1(iN)时, 式(5) 变为式(3);当α=λ=1, λ1=$\frac{1}{q}$, λ2=$\frac{1}{p}$时, 式(5) 变为式(2).

 ${\omega _\alpha }\left( {\sigma ,x} \right): = \sum\limits_{n = 1}^\infty {\frac{{{v_n}}}{{{{\left( {1 + {U^\alpha }\left( x \right)V_n^\alpha } \right)}^\lambda }}}} \frac{{{U^\sigma }\left( x \right)}}{{V_n^{1 - \sigma }}},x \in {{\bf{R}}_ + },$ (6)
 ${{\tilde \omega }_\alpha }\left( {\sigma ,x} \right): = \int_0^\infty {\frac{{\mu \left( x \right)}}{{{{\left( {1 + {U^\alpha }\left( x \right)V_n^\alpha } \right)}^\lambda }}}\frac{{V_n^\sigma }}{{{U^{1 - \sigma }}\left( x \right)}}{\rm{d}}x} ,n \in {\bf{N}},$ (7)

 ${\omega _\alpha }\left( {\sigma ,x} \right) < {k_\alpha }\left( \sigma \right)\left( {x \in {{\bf{R}}_ + };0 < \sigma < \alpha \lambda ,\sigma \le 1} \right),$ (8)
 ${{\tilde \omega }_\alpha }\left( {\sigma ,n} \right) \le {k_\alpha }\left( \sigma \right)\left( {x \in {\bf{N}};0 < \sigma < \alpha \lambda } \right).$ (9)

 $\begin{array}{l} {\omega _\alpha }\left( {\sigma ,x} \right) = \sum\limits_{n = 1}^\infty {\int_{n - 1}^n {\frac{{V'\left( t \right)}}{{{{\left( {1 + {U^\alpha }\left( x \right)V_n^\alpha } \right)}^\lambda }}}\frac{{{U^\sigma }\left( x \right)}}{{V_n^{1 - \sigma }}}{\rm{d}}t} } < \\ \;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\sum\limits_{n = 1}^\infty {\int_{n - 1}^n {\frac{{V'\left( t \right)}}{{{{\left( {1 + {U^\alpha }\left( x \right){V^\alpha }\left( t \right)} \right)}^\lambda }}}\frac{{{U^\sigma }\left( x \right)}}{{V_n^{1 - \sigma }}}{\rm{d}}t} } . \end{array}$

 $\begin{array}{l} {\omega _\alpha }\left( {\sigma ,x} \right) < \frac{1}{\alpha }\sum\limits_{n = 1}^\infty {\int_{{U^\alpha }\left( x \right){V^\alpha }\left( {n - 1} \right)}^{{U^\alpha }\left( x \right){V^\alpha }\left( n \right)} {\frac{{{u^{\left( {\sigma /a} \right) - 1}}}}{{{{\left( {1 + u} \right)}^\lambda }}}{\rm{d}}u} } = \\ \;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\frac{1}{\alpha }\int_0^{{U^\alpha }\left( x \right){V^\alpha }\left( \infty \right)} {\frac{{{u^{\left( {\sigma /a} \right) - 1}}}}{{{{\left( {1 + u} \right)}^\lambda }}}{\rm{d}}u} \le \\ \;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\frac{1}{\alpha }\int_0^\infty {\frac{{{u^{\left( {\sigma /a} \right) - 1}}}}{{{{\left( {1 + u} \right)}^\lambda }}}{\rm{d}}u} = {k_\alpha }\left( \sigma \right). \end{array}$

 $\begin{array}{l} {{\tilde \omega }_\alpha }\left( {\sigma ,n} \right) = \frac{1}{\alpha }\int_0^{V_n^\alpha {U^\alpha }\left( \infty \right)} {\frac{{{t^{\left( {\sigma /a} \right) - 1}}}}{{{{\left( {t + 1} \right)}^\lambda }}}{\rm{d}}t} \le \\ \;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\frac{1}{\alpha }\int_0^\infty {\frac{{{t^{\left( {\sigma /a} \right) - 1}}}}{{{{\left( {t + 1} \right)}^\lambda }}}{\rm{d}}t} = {k_\alpha }\left( \sigma \right). \end{array}$

 $\sum\limits_{n = 1}^\infty {\frac{{{v_n}}}{{V_n^{1 + \varepsilon }}}} = \frac{1}{\varepsilon }\left( {1 + o\left( 1 \right)} \right)\left( {\varepsilon \to {0^ + }} \right).$ (10)

 $\begin{array}{l} \sum\limits_{n = 1}^\infty {\frac{{{v_n}}}{{V_n^{1 + \varepsilon }}}} = \frac{1}{{v_1^\varepsilon }} + \sum\limits_{n = 2}^\infty {\int_{n - 1}^n {\frac{{V'\left( t \right)}}{{{V^{1 + \varepsilon }}\left( n \right)}}{\rm{d}}t} } \le \\ \;\;\;\;\;\;\;\;\;\;\;\;\;\;\frac{1}{{v_1^\varepsilon }} + \sum\limits_{n = 2}^\infty {\int_{n - 1}^n {\frac{{V'\left( t \right)}}{{{V^{1 + \varepsilon }}\left( t \right)}}{\rm{d}}t} } = \\ \;\;\;\;\;\;\;\;\;\;\;\;\;\;\frac{1}{{v_1^\varepsilon }} + \sum\limits_{n = 2}^\infty {\int_{V\left( {n - 1} \right)}^{V\left( n \right)} {\frac{{{\rm{d}}u}}{{{u^{1 + \varepsilon }}}}} } = \frac{1}{{v_1^\varepsilon }} + \int_{{v_1}}^\infty {\frac{{{\rm{d}}u}}{{{u^{1 + \varepsilon }}}}} = \\ \;\;\;\;\;\;\;\;\;\;\;\;\;\;\frac{1}{\varepsilon }\left[ {1 + \left( {\frac{1}{{v_1^\varepsilon }} + \frac{\varepsilon }{{v_1^\varepsilon }} - 1} \right)} \right], \end{array}$
 $\begin{array}{l} \sum\limits_{n = 1}^\infty {\frac{{{v_n}}}{{V_n^{1 + \varepsilon }}}} \ge \sum\limits_{n = 1}^\infty {\int_n^{n + 1} {\frac{{{V_{n + 1}}}}{{V_n^{1 + \varepsilon }}}{\rm{d}}t} } = \\ \;\;\;\;\;\;\;\;\;\;\;\;\;\;\sum\limits_{n = 1}^\infty {\int_n^{n + 1} {\frac{{V'\left( t \right)}}{{V_n^{1 + \varepsilon }}}{\rm{d}}t} } > \sum\limits_{n = 1}^\infty {\int_n^{n + 1} {\frac{{{\rm{d}}V\left( t \right)}}{{{V^{1 + \varepsilon }}\left( t \right)}}} } = \\ \;\;\;\;\;\;\;\;\;\;\;\;\;\;\sum\limits_{n = 1}^\infty {\int_{V\left( n \right)}^{V\left( {n + 1} \right)} {\frac{{{\rm{d}}u}}{{{u^{1 + \varepsilon }}}}} } = \int_{{v_1}}^\infty {\frac{{{\rm{d}}u}}{{{u^{1 + \varepsilon }}}}} = \\ \;\;\;\;\;\;\;\;\;\;\;\;\;\;\frac{1}{\varepsilon }\left[ {1 + \left( {\frac{1}{{v_1^\varepsilon }} - 1} \right)} \right], \end{array}$

 $\begin{array}{l} I: = \sum\limits_{n - 1}^\infty {\int_0^\infty {\frac{{{a_n}f\left( x \right)}}{{\left( {1 + {U^\alpha }\left( x \right)V_n^\alpha } \right)}}{\rm{d}}x} } < \frac{1}{\alpha }B\left( {\frac{{\alpha \lambda - \sigma }}{\alpha },\frac{\sigma }{\alpha }} \right) \times \\ \;\;\;{\left[ {\int_0^\infty {\frac{{{{\left( {U\left( x \right)} \right)}^{p\left( {1 - \sigma } \right) - 1}}}}{{{\mu ^{p - 1}}\left( x \right)}}{f^p}\left( x \right){\rm{d}}x} } \right]^{\frac{1}{p}}}{\left[ {\sum\limits_{n = 1}^\infty {\frac{{V_n^{q\left( {1 - \sigma } \right) - 1}}}{{v_n^{q - 1}}}a_n^q} } \right]^{\frac{1}{q}}}, \end{array}$ (11)
 $\begin{array}{l} {J_1}: = {\left\{ {\sum\limits_{n = 1}^\infty {\frac{{{v_n}}}{{V_n^{1 - p\sigma }}}{{\left[ {\int_0^\infty {\frac{{f\left( x \right)}}{{{{\left( {1 + {U^\alpha }\left( x \right)V_n^\alpha } \right)}^\lambda }}}{\rm{d}}x} } \right]}^p}} } \right\}^{\frac{1}{p}}} < \\ \;\;\;\;\;\frac{1}{\alpha }B\left( {\frac{{\alpha \lambda - \sigma }}{\alpha },\frac{\sigma }{\alpha }} \right){\left[ {\int_0^\infty {\frac{{{{\left( {U\left( x \right)} \right)}^{p\left( {1 - \sigma } \right) - 1}}}}{{{\mu ^{p - 1}}\left( x \right)}}{f^p}\left( x \right){\rm{d}}x} } \right]^{\frac{1}{p}}}, \end{array}$ (12)
 $\begin{array}{*{20}{c}} {{J_2}: = {{\left\{ {\int_0^\infty {\frac{{\mu \left( x \right)}}{{{{\left( {U\left( x \right)} \right)}^{1 - q\sigma }}}}\sum\limits_{n - 1}^\infty {{{\left[ {\frac{{{a_n}}}{{{{\left( {1 + {U^\alpha }\left( x \right)V_n^\alpha } \right)}^\lambda }}}} \right]}^q}} {\rm{d}}x} } \right\}}^{\frac{1}{q}}} < }\\ {\frac{1}{\alpha }B\left( {\frac{{\alpha \lambda - \sigma }}{\alpha },\frac{\sigma }{\alpha }} \right){{\left[ {\sum\limits_{n = 1}^\infty {\frac{{V_n^{q\left( {1 - \sigma } \right) - 1}}}{{v_n^{q - 1}}}a_n^q} } \right]}^{\frac{1}{q}}}.} \end{array}$ (13)

 $\begin{array}{l} {\left[ {\int_0^\infty {\frac{{f\left( x \right)}}{{{{\left( {1 + {U^\alpha }\left( x \right)V_n^\alpha } \right)}^\lambda }}}{\rm{d}}x} } \right]^p} = \\ \;\;\;\;\;\;\left[ {\int_0^\infty {\frac{1}{{{{\left( {1 + {U^\alpha }\left( x \right)V_n^\alpha } \right)}^\lambda }}}} \left( {\frac{{V_n^{\left( {1 - \sigma } \right)/p}{\mu ^{1/q}}\left( x \right)}}{{{U^{\left( {1 - \sigma } \right)/q}}\left( x \right)v_n^{1/p}}}} \right) \times } \right.\\ \;\;\;\;\;\;{\left. {\left( {\frac{{{U^{\left( {1 - \sigma } \right)/q}}\left( x \right)v_n^{1/p}}}{{V_n^{\left( {1 - \sigma } \right)/p}{\mu ^{1/q}}\left( x \right)}}f\left( x \right)} \right){\rm{d}}x} \right]^p} \le \\ \;\;\;\;\;\;\left[ {\int_0^\infty {\frac{1}{{{{\left( {1 + {U^\alpha }\left( x \right)V_n^\alpha } \right)}^\lambda }}}} \frac{{{U^{\left( {1 - \sigma } \right)p/q}}\left( x \right){v_n}}}{{V_n^{\left( {1 - \sigma } \right)}{\mu ^{p/q}}\left( x \right)}}{f^p}\left( x \right){\rm{d}}x} \right] \times \\ \;\;\;\;\;\;{\left[ {\int_0^\infty {\frac{1}{{{{\left( {1 + {U^\alpha }\left( x \right)V_n^\alpha } \right)}^\lambda }}}} \frac{{V_n^{\left( {1 - \sigma } \right)q/p}\mu \left( x \right)}}{{{U^{1 - \sigma }}\left( x \right)v_n^{q/p}}}{\rm{d}}x} \right]^{p/q}} = \\ \;\;\;\;\;\;{\left( {{{\tilde \omega }_\alpha }\left( {\sigma ,n} \right)} \right)^{p - 1}}\frac{{V_n^{1 - p\sigma }}}{{{v_n}}}\int_0^\infty {\frac{1}{{{{\left( {1 + {U^\alpha }\left( x \right)V_n^\alpha } \right)}^\lambda }}}} \times \\ \;\;\;\;\;\;\frac{{{{\left( {U\left( x \right)} \right)}^{\left( {1 - \sigma } \right)p/q}}{v_n}}}{{V_n^{1 - \sigma }{\mu ^{p/q}}\left( x \right)}}{f^p}\left( x \right){\rm{d}}x. \end{array}$ (14)

 $\begin{array}{l} {J_1} \le {\left( {{k_\alpha }\left( \sigma \right)} \right)^{\frac{1}{q}}}\left[ {\sum\limits_{n = 1}^\infty {\int_0^\infty {\frac{1}{{{{\left( {1 + {U^\alpha }\left( x \right)V_n^\alpha } \right)}^\lambda }}}} } \times } \right.\\ \;\;\;\;\;\;\;\;{\left. {\frac{{{{\left( {U\left( x \right)} \right)}^{\left( {1 - \sigma } \right)\left( {p - 1} \right)}}{v_n}}}{{V_n^{1 - \sigma }{\mu ^{p - 1}}\left( x \right)}}{f^p}\left( x \right){\rm{d}}x} \right]^{\frac{1}{p}}} = \\ \;\;\;\;\;\;\;\;{\left( {{k_\alpha }\left( \sigma \right)} \right)^{\frac{1}{q}}}\left[ {\int_0^\infty {\sum\limits_{n = 1}^\infty {\frac{1}{{{{\left( {1 + {U^\alpha }\left( x \right)V_n^\alpha } \right)}^\lambda }}}} } \times } \right.\\ \;\;\;\;\;\;\;\;{\left. {\frac{{{{\left( {U\left( x \right)} \right)}^{\left( {1 - \sigma } \right)\left( {p - 1} \right)}}{v_n}}}{{V_n^{1 - \sigma }{\mu ^{p - 1}}\left( x \right)}}{f^p}\left( x \right){\rm{d}}x} \right]^{\frac{1}{p}}} = \\ \;\;\;\;\;\;\;\;{\left( {{k_\alpha }\left( \sigma \right)} \right)^{\frac{1}{q}}}{\left[ {\int_0^\infty {{\omega _\alpha }\left( {\sigma ,x} \right)\frac{{{{\left( {U\left( x \right)} \right)}^{p\left( {1 - \sigma } \right) - 1}}}}{{{\mu ^{p - 1}}\left( x \right)}}{f^p}\left( x \right){\rm{d}}x} } \right]^{\frac{1}{p}}}. \end{array}$ (15)

 $\begin{array}{l} I = \sum\limits_{n = 1}^\infty {\left[ {\frac{{v_n^{1/p}}}{{V_n^{\frac{1}{p} - \sigma }}}\int_0^\infty {\frac{{f\left( x \right)}}{{{{\left( {1 + {U^\alpha }\left( x \right)V_n^\alpha } \right)}^\lambda }}}{\rm{d}}x} } \right]\left[ {\frac{{V_n^{\frac{1}{p} - \sigma }}}{{v_n^{1/p}}}{a_n}} \right]} \le \\ \;\;\;\;\;\;{J_1}{\left[ {\sum\limits_{n = 1}^\infty {\frac{{V_n^{q\left( {1 - \sigma } \right) - 1}}}{{v_n^{q - 1}}}a_n^q} } \right]^{\frac{1}{q}}}. \end{array}$ (16)

 ${a_n} = \frac{{{v_n}}}{{V_n^{1 - p\sigma }}}{\left[ {\int_0^\infty {\frac{{f\left( x \right)}}{{{{\left( {1 + {U^\alpha }\left( x \right)V_n^\alpha } \right)}^\lambda }}}{\rm{d}}x} } \right]^{p - 1}},n \in {\bf{N}},$

J1=${[\sum\limits_{n = 1}^\infty {\frac{{{V_n}^{q(1-\sigma )-1}}}{{{\nu _n}^{q-1}}}} {a_n}^q]^{\frac{1}{p}}}$.若J1=0, 则式(12) 自然成立; 若J=∞, 因ωα(σ, x) < kα(σ), 则式(15) 不成立.可设0 < J1 < ∞.由式(11), 有

 $\begin{array}{l} \sum\limits_{n = 1}^\infty {\frac{{V_n^{q\left( {1 - \sigma } \right) - 1}}}{{v_n^{q - 1}}}a_n^q} = J_1^p = I < \\ {k_\alpha }\left( \sigma \right){\left[ {\int_0^\infty {\frac{{{{\left( {U\left( x \right)} \right)}^{p\left( {1 - \sigma } \right) - 1}}}}{{{\mu ^{p - 1}}\left( x \right)}}{f^p}\left( x \right){\rm{d}}x} } \right]^{\frac{1}{p}}}{\left[ {\sum\limits_{n = 1}^\infty {\frac{{V_n^{q\left( {1 - \sigma } \right) - 1}}}{{v_n^{q - 1}}}b_n^q} } \right]^{\frac{1}{q}}},\\ {J_1}{\left[ {\sum\limits_{n = 1}^\infty {\frac{{V_n^{q\left( {1 - \sigma } \right) - 1}}}{{v_n^{q - 1}}}a_n^q} } \right]^{\frac{1}{q}}} < \\ \;\;\;\;{k_\alpha }\left( \sigma \right){\left[ {\int_0^\infty {\frac{{{{\left( {U\left( x \right)} \right)}^{p\left( {1 - \sigma } \right) - 1}}}}{{{\mu ^{p - 1}}\left( x \right)}}{f^p}\left( x \right){\rm{d}}x} } \right]^{\frac{1}{p}}}. \end{array}$

 $\begin{array}{l} \int_0^\infty {\frac{{{{\left( {U\left( x \right)} \right)}^{p\left( {1 - \sigma } \right) - 1}}}}{{{\mu ^{p - 1}}\left( x \right)}}} {{\tilde f}^p}\left( x \right){\rm{d}}x = \\ \;\;\;\;\;\;\;\;\;\;\;\;\int_0^{{U^{ - 1}}\left( 1 \right)} {{{\left( {U\left( x \right)} \right)}^{ - 1 + \varepsilon }}{\rm{d}}U\left( x \right)} = \frac{1}{\varepsilon },\\ \;\;\;\;\;\sum\limits_{n = 1}^\infty {\frac{{V_n^{q\left( {1 - \sigma } \right) - 1}}}{{v_n^{q - 1}}}\tilde a_n^q} = \sum\limits_{n = 1}^\infty {\frac{{{v_n}}}{{V_n^{1 + \varepsilon }}}} = \frac{1}{\varepsilon }\left( {1 + o\left( 1 \right)} \right),\\ \tilde I: = \sum\limits_{n = 1}^\infty {\int_0^\infty {\frac{{{{\tilde a}_n}f\left( x \right)}}{{{{\left( {1 + {U^\alpha }\left( x \right)V_n^\alpha } \right)}^\lambda }}}{\rm{d}}x} } = \\ \sum\limits_{n = 1}^\infty {\left[ {\int_0^{{U^{ - 1}}\left( 1 \right)} {\frac{{\mu \left( x \right)}}{{{{\left( {1 + {U^\alpha }\left( x \right)V_n^\alpha } \right)}^\lambda }}}\frac{{V_n^{\tilde \sigma }}}{{{{\left( {U\left( x \right)} \right)}^{1 - \tilde \sigma }}}}{\rm{d}}x} } \right]\frac{{{v_n}}}{{V_n^{\varepsilon + 1}}}} = \\ \sum\limits_{n = 1}^\infty {\left[ {{{\tilde \omega }_\alpha }\left( {\tilde \sigma ,n} \right) - \int_{{U^{ - 1}}\left( 1 \right)}^\infty {\frac{{\mu \left( x \right)}}{{{{\left( {1 + {U^\alpha }\left( x \right)V_n^\alpha } \right)}^\lambda }}}\frac{{V_n^{\tilde \sigma }}}{{{{\left( {U\left( x \right)} \right)}^{1 - \tilde \sigma }}}}{\rm{d}}x} } \right]\frac{{{v_n}}}{{V_n^{\varepsilon + 1}}}} \ge \\ \sum\limits_{n = 1}^\infty {\left[ {{k_\alpha }\left( {\tilde \sigma } \right) - \int_{{U^{ - 1}}\left( 1 \right)}^\infty {\frac{1}{{{U^{\alpha \lambda }}\left( x \right)V_n^{\alpha \lambda }}}\frac{{V_n^{\tilde \sigma }}}{{{{\left( {U\left( x \right)} \right)}^{1 - \tilde \sigma }}}}{\rm{d}}U\left( x \right)} } \right]} \frac{{{v_n}}}{{V_n^{\varepsilon + 1}}} = \\ {k_\alpha }\left( {\tilde \sigma } \right)\left[ {\sum\limits_{n = 1}^\infty {\frac{{{v_n}}}{{V_n^{1 + \varepsilon }}}} - \frac{1}{{\left( {\alpha \lambda - \tilde \sigma } \right){k_\alpha }\left( {\tilde \sigma } \right)}}\sum\limits_{n = 1}^\infty {\frac{{{v_n}}}{{V_n^{\left( {\varepsilon /q} \right) + \alpha \lambda - \sigma + 1}}}} } \right] = \\ \frac{1}{\varepsilon } \cdot \frac{1}{\alpha }B\left( {\frac{{\alpha \lambda - \tilde \sigma }}{\alpha },\frac{{\tilde \sigma }}{\alpha }} \right)\left( {1 + o\left( 1 \right) - \varepsilon O\left( 1 \right)} \right). \end{array}$ (17)

 $\begin{array}{l} \varepsilon \sum\limits_{n = 1}^\infty {\int_0^\infty {\frac{{{{\tilde a}_n}\tilde f\left( x \right)}}{{{{\left( {1 + {U^\alpha }\left( x \right)V_n^\alpha } \right)}^\lambda }}}{\rm{d}}x} } < \\ \varepsilon K{\left[ {\int_0^\infty {\frac{{{{\left( {U\left( x \right)} \right)}^{p\left( {1 - \sigma } \right) - 1}}}}{{{\mu ^{p - 1}}\left( x \right)}}{{\tilde f}^p}\left( x \right){\rm{d}}x} } \right]^{\frac{1}{p}}}{\left[ {\sum\limits_{n = 1}^\infty {\frac{{V_n^{q\left( {1 - \sigma } \right) - 1}}}{{v_n^{q - 1}}}\tilde a_n^q} } \right]^{\frac{1}{q}}}. \end{array}$

 $\begin{array}{l} \frac{1}{\alpha }B\left( {\frac{{\alpha \lambda - \tilde \sigma }}{\alpha },\frac{{\tilde \sigma }}{\alpha }} \right)\left( {1 + o\left( 1 \right) - \varepsilon O\left( 1 \right)} \right) < K{\left( {1 + o\left( 1 \right)} \right)^{\frac{1}{q}}},\\ 即有\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;{k_\alpha }\left( \sigma \right) \le K\left( {\varepsilon \to {0^ + }} \right). \end{array}$

K=kα(σ)为式(11) 的最佳值.

 [1] HARDY G H. Note on a theorem of Hilbert concerning series of positive terms[J]. Proceedings London Math Soc, 1925, 23(2):Records of Proc xlv-xlvi. [2] HARDY G H, LITTLEWOOD J E, POLYA G. Inequalities[M]. Cambridge: Cambridge University Press, 1952. [3] YANG B C. On best extensions of Hardy-Hilbert's inequality with two parameters[J]. Journal of Inequalities in Pure and Applied Mathematics, 2005, 6(3):Article No 81. [4] 王竹溪, 郭敦仁. 特殊函数论[M]. 北京: 科学出版社, 1979. WANG Z X, GUO D R. Introduction of Particular Functions[M]. Beijing: Science Press, 1979. [5] 杨必成. 算子范数与Hilbert型不等式[M]. 北京: 科学出版社, 2009. YANG B C. The Norm of Operator and Hilbert-Type Inequalities[M]. Beijing: Science Press, 2009. [6] YANG B C. Discrete Hilbert-type Inequalities[M]. Sharjah: Bentham Science Publishers, 2011. [7] 杨必成. 一个推广的Hardy-Hilbert型不等式[J]. 广东第二师范学院学报, 2015, 35(3): 1–8. YANG B C. An extension of Hardy-Hilbert-type inequality[J]. Journal of Guangdong University of Education, 2015, 35(3): 1–8. [8] 杨必成, 陈强. 一个半离散含多参数的Hilbert型不等式[J]. 浙江大学学报:理学版, 2012, 39(6): 623–626. YANG B C, CHEN Q. A half-discrete Hilbert-type inequality with multi-parameters[J]. Journal of Zhejiang University: Science Edition, 2012, 39(6): 623–626. [9] HUANG Q L, WANG A Z, YANG B C. A more accurate half-discrete Hilbert-type inequality with a general non-homogeneous kernel and operator expressions[J]. Mathematical Inequalities and Applications, 2014, 17(1): 367–388. [10] WANG A Z, YANG B C. A more accurate reverse half-discrete Hilbert-type inequality[J]. Journal of Inequalities and Applications, 2015: 85. DOI:10.1186/s13660-015-0613-8 [11] YANG B C, DEBNATH L. Half-Discrete Hilbert-Type Inequalities[M]. Singapore: World Scientific Publishing Co Pte Ltd, 2014. [12] 匡继昌. 常用不等式[M]. 济南: 山东科技出版社, 2004. KUANG J C. Applied Inequalities[M]. Jinan: Shandong Science and Technology Press, 2004. [13] 匡继昌. 实变函数与泛函分析(续论)[M]. 北京: 高等教育出版社, 2015. KUANG J C. Real Functions and Functional Analysis (Continuous)[M]. Beijing: Higher Education Press, 2015.